RELIGION AND THE STATUS OF NIGERIAN WOMEN - Onwurah, Emeka (Journal of Dharma, 1988)
In the old, old days .. , women were more powerful than the men, for to them alone the mysteries of the god and of secret things were made known. By such knowledge they were enabled to keep all males as servants, employing them to do the heaviest work. Especially because of the strength of their limbs and greater endurance were men found useful as fighters. Now at first women greatly outnumber men upon earth, but after a while the latter began to multiply and in course of time they grew discontented with their lot.